Best practice in clinical simulation education − are we there yet? A cross-sectional survey of simulation in Australian and New Zealand pre-registration nursing education. Issue 3 (June 2018) - Bogossian, Fiona; Cooper, Simon; Kelly, Michelle; Levett-Jones, Tracy; McKenna, Lisa; Slark, Julia; Seaton, Philippa
Abstract: Background: Simulation is potentially a means of increasing clinical education capacity. Significant investments have been made in simulation but the extent to which this has improved uptake, quality and diversity of simulation use is unclear. Aim: To describe the current use of simulation in tertiary nursing education programs leading to nurse registration Australia and New Zealand, and determine whether investments in simulation have improved uptake, quality and diversity of simulation experiences. Methods: A cross sectional electronic survey distributed to lead nursing academics in programs leading to nurse registration in Australia and New Zealand. Findings: 51.6% of institutions responded and reported wide variation in allocation of program hours to clinical and simulation learning. Simulation was embedded in curricula and positively valued as an adjunct or substitute for clinical placement. While simulation environments were adequate, staff time, training and resource development were barriers to increasing the quality, amount and range of simulation experiences. Quality assurance and robust evaluation were weak. Discussion: Simulation program hours are inconsistently reported and underutilized in terms of potential contribution to clinical learning. Benefits of capital investment in simulation physical resources have been realised, but barriers persist for increasing high quality simulation in nursing programs. Conclusion: Transitioning components of clinical education from the clinical to tertiary sectors has resource implications. Establishment of sustainable, high quality simulation experiences requires staff training, shared resources, best practice and robust evaluation of simulation experiences in nursing curricula.